PENGARUH PERILAKU HIDUP BERSIH DAN SEHAT (PHBS), PENDAPATAN DAN SANITASI TERHADAP KEJADIAN DIARE DI KELURAHAN MERANTI PANDAK, RUMBAI PESISIR PEKANBARU - Noni Febriza; Usman M. Tang; Esy Maryanti (Jurnal Ilmu Lingkungan, 2015)
This study aims to analyze the influence of behavior, income and sanitation on theincidence of diarrhea. This research is a field survey using cross sectional method withsampling proportional stratified random sampling with a sample of 96 families . Thevariables measured were PHBs , income and sanitation (latrines and drinking water) tothe incidence of diarrhea. The results showed that the views of the multiple logisticregression can be concluded that all the independent variables of the study effect on theincidence of diarrhea. Most influential variable is the variable that is the type ofsanitary water storage with p value 0.000